Evaluating transferability of flow–ecology relationships across space, time and taxonomy. (16th October 2017) - Chen, William; Olden, Julian D.
Abstract: Environmental flow assessments are becoming increasingly central to ecologically‐sustainable river management. Rigorous evaluations of flow–ecology relationships serve a vital role in guiding these assessments to meet targeted ecosystem objectives. However, limited resources and widespread environmental change are outpacing the ability to gain knowledge of species' flow responses and assess environmental needs for rivers individually. Successfully transferring flow–ecology relationships across space and time would facilitate regional‐scale environmental flow assessments, yet the necessary contexts for such success remains a knowledge gap. Here, we leverage long‐term, multi‐species datasets across multiple river basins in southwestern United States as a case study to explore whether relationships between species abundances and hydrological conditions are transferable across space and time. Additionally, we evaluate the potential for ecological guilds based on fluvial dependence and life‐history strategies to facilitate the transfer of flow–ecology knowledge across taxonomic boundaries. Species varied in the spatial transferability of their flow–ecology relationships. Spatial transferability was similar when comparing a species' flow–ecology relationships within a river basin versus across different river basins, although transferability was considerably greater across free‐flowing rivers compared to regulated rivers. Species' flow–ecology relationships transferred through time just as well as across space. Ecological guilds defined according to fluvial dependence and life‐history strategies offered just as much potential for transferring flow–ecology knowledge among species as transferring within species across space or time. Our study provides insights into transferring flow–ecology knowledge to support effective, regional‐scale environmental flows. Further research into developing transferable flow–ecology relationships for a wide range of environmental predictors and biological responses across different spatial scales and flow regimes will enable us to keep pace with the increasing demand for science to inform sustainable river management.